Children with ADHD and their teachers: A review of the literature - Kos, J.; Richdale, A.; Hay, David (Routledge, 2006)
There is considerable evidence regarding the academic and social difficulties children with Attention Deficit Hyperactivity Disorder (ADHD) experience, but less is known about what their teachers do and should know. This article provides a summary of this evidence, including information on the difficulties experienced by students with ADHD, the relationships between teachers and students with ADHD, pre‐service and in‐service teachers' knowledge and attitudes toward ADHD, and in‐service teachers' behaviour toward children diagnosed with the condition. Teachers need increased awareness of the family circumstances of children with ADHD, more knowledge of the conditions commonly comorbid with ADHD, and insight into these children's relationship with peers.